Uji Efektivitas Teknik Ekstraksi dan Dry Heat Treatmentterhadap Kesehatan Bibit Tomat (Lycopersicum esculentum Mill.) - DEWA NYOMAN PREMA ANANDA; I GUSTI NGURAH RAKA; NI NYOMAN ARI MAYADEWI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
ABSTRACT Effectiveness of Technique Extraction Test and Dry Heat Treatment to Seed Health of Tomato (Lycopersicum esculentum Mill.). Tomato (Lycopersicum esculentum Mill.) is one of horticultural commodities with many benefit and still requires serious treatment for improvement of productivity.Seed healthy is one of the tomato productivitydeterminer. Tomato seeds used by farmers mostly contaminated by seed-borne viruses.This research aims to determine the effectiveness of extraction technique and dry heat treatment on the health of tomato seedlings. Research consists of five activities: 1. Fruit prepation for seed; 2. Extraction of seeds; 3. Drying; 4. Dry heat tratment, 5. Seed quality testing; and 6. Data analisys. This research is completely randomized design (CRD) with six treatment combinations and each combination is repeated four times. The results showed extraction treatment with soaking 2% HCl, calcium oxide, and water is not effective to produce healthy tomato seedlings, while Dry Heat Treatment effective to produce healthy tomato seedlings. Extraction and treatment of Dry Heat Treatment show interaction on seed health variables were real derived from diseased plants. Keywords: tomato, extraction techniques, dry heat,seedlings healthy